Profit Quality Analysis of Investment Opportunity Set, Leverage, and Good Corporate Governance - Wardani, Indry Maura Kusuma; Fidiana, Fidiana (Akuntansi: Jurnal Akuntansi Integratif, 2023)
This research is motivated by the company's investment decisions during the pandemic to increase its business scale in the future which gives investor’s confidence in making financial decisions. The purpose of current study is to investigate how profit quality is impacted by good corporate governance, leverage as well as investment opportunity sets. The DER was used to measure the leverage, the market book value of asset ratio was used to measure the IOS, and the proportion and quantity of firms' ownership of the audit committee, independent commissioner board, managerial ownership, and institutional ownership were all used to measure GCG. It was a quantitative study. Food and beverage businesses that were listed on the IDX (Indonesia Stock Exchange) also made up the population. The method of gathering data employed purposive sampling. 13 businesses made up the sample in accordance with that. Moreover, the data was collected during a three-year period (2019–2021). 39 pieces of data in all were examined. The t-test, F-test, R2 test, and multiple linear regression were also employed in the data analysis technique. The outcome showed that there was a negative correlation between profit quality and the set of investment opportunities. On the other hand, managerial ownership improved the quality of profits. On the other hand, the quality of profits was unaffected by leverage, institutional ownership, the independent commissioner board, and the audit committee. These results imply the failure of all sample firms to achieve positive returns on their investment sets in assets during the pandemic. Not a single firm was able to show positive prospects for investment opportunities during the pandemic.